PERHITUNGAN WETON DALAM PERNIKAHAN ADAT JAWA PERSPEKTIF MAQOSHID SYARI’AH (AL MUNAZHZHARAH, 2021)
Until now, Javanese customs can be found in various places. The calculation of weton in marriage which means the birthday and market of a man and a woman are combined to find a good day in marriage. Such customs can be found in Jugo Village, Mojo District, Kediri Regency, as evidenced by the presence of couples who married in 2020 using weton in their marriages, as an effort to make the household in the future last and as an effort to minimize the occurrence of impermanence in the household. This study uses a type of field study (flied research) with a descriptive qualitative approach using primary data from interviews with informants and supported by primary, secondary and tertiary legal materials. The data collection procedure used is the interview and documentation method. The researcher uses the persistence of observations and detailed descriptions using literacy materials so that they can support the credibility of the data presented by the researchers. The results of the study are that the majority of weton calculations in marriage in Jugo Village are used to find auspicious days in marriage, in addition to weton calculations there are also prohibitions on marriage such as the number of wetons between the bride and groom is the same, it is not allowed for couples who meet weton Tuesday wage and jum'ah pahing and It is not permissible to marry on the same day and market as the parents of the bride and groom. This is a law that is not codified but the law lives in the community which is categorized as customary law. If it is related to the prohibitions that should not be violated in the calculation of the weton, in fact it can still be found a way out without the marriage being annulled. If viewed from the perspective of Maqashid Syari'ah, the custom of calculating Weton in marriage is included in the category of hajiyat needs, which can be abandoned by the community but will cause difficulties if you do not carry out the custom.